Optimising CRISPR for targeting of primary haematopoietic stem cells - Field, L (2021)
CRISPR (clustered regularly interspaced short palindromic repeats) offers an unprecedented array of genetic tools for treating and modelling haematological disorders. However, there are concerns about its safety. CRISPR-based editing can induce upregulation of TP53 associated pathways, a finding particularly important for clinical applications. The impact of CRISPR-based editing on haematopoietic stem cells (HSCs) has not, however, been interrogated in detail.